IMMIGRANTS AT THE AMERICAN LABOR MARKET - N. Petrovskaya (Вестник университета, 2016)
The article provides analysis of basic immigration trends in US, with focus on foreign born persons employment, their participation in the American labor force; immigrant’s unemployment. It also examines main peculiarities of US immigration policy.